Rhetorical Strategies and Genre Conventions in Literary Studies: Teaching and Writing in the Disciplines - Wilder, Laura (Southern Illinois University Press, 2012)
Laura Wilder fills a gap in the scholarship on writing in the disciplines and writing across the curriculum with this thorough study of the intersections between scholarly literary criticism and undergraduate writing in introductory literature courses. Rhetorical Strategies and Genre Conventions in Literary Studies is the first examination of rhetorical practice in the research and teaching of literary study and a detailed assessment of the ethics and efficacy of explicit instruction in the rhetorical strategies and genre conventions of the discipline. Using rhetorical analysis, ethnographic observation, and individual interviews, Wilder demonstrates how rhetorical conventions play a central, although largely tacit, role in the teaching of literature and the evaluation of student writing. Wilder follows a group of literature majors and details their experiences. Some students received experimental, explicit instruction in the special topoi, while others received more traditional, implicit instruction. Arguing explicit instruction in disciplinary conventions has the potential to help underprepared students, Wilder explores how this kind of instruction may be incorporated into literature courses without being overly reductive. Taking into consideration student perspectives, Wilder makes a bold case for expanding the focus of research in writing in the disciplines and writing across the curriculum in order to grasp the full complexity of disciplinary discourse.